Development of Teaching Materials on Learning Economic Models to Improve Students’ Cognitive Achievement - Zuhri Saputra Hutabarat; Ekawarna Ekawarna (AL-ISHLAH: Jurnal Pendidikan, 2023)
The objectives of this research are to both produce products of teaching materials of Learning Economic Models and find their effects towards students’ cognitive achievement. Dick and Carey’s model was used for the concept of the development model. Formative tests were used to measure the effectiveness of teaching materials-and they were used to test one evaluation, small group evaluation, and field trial. The data collected was analyzed through mean, standard deviation, and z-test statistics. The research showed the products of teaching materials, with all being covered from Chapter 1 through Chapter 8 in order: 1) the theory of teaching and learning, 2) the basic concept learning models, 3) science-based learning models, 4) innovative learning models, 5) cooperative and collaborative learning models, 6) a model of problem-based learning, 7) contextual-based learning models, and 8) integrated learning models. The findings revealed that students with the teaching materials performed better than those without. The null hypothesis was tested at a 0.05 level of significance, indicating a significant difference between the cognitive achievement scores of those taught with the teaching materials and those taught without.